GETARAN TANAH AKIBAT PELEDAKAN PADA JARAK AMAN KURANG DARI 300 METER TERHADAP MANUSIA DAN BANGUNAN DI KUARI BATUGAMPING PT LEBAK ENERGI NUSANTARA BAYAH KABUPATEN LEBAK PROVINSI BANTEN - Adinugraha, Wanda; Suwandhi, Awang; Marmer, Dwihandoyo; Hadiyat, Yudiana (PPSDM Geominerba, 2023)
The limestone quarry managed by PT Lebak Energi Nusantara (PT LEN) is located at Bayah, Lebak regency, Banten province. Blasting techniques are used to break limestone from its rock mass. In connection with the progress of mining which is getting closer to public facilities, a technical study of the impact of blasting is needed. Mining progress is a critical issue because the impact of blasting vibrations can affect the stability of buildings and disturb residents around the quarry. The buildings around the blasting are classified as class 3 because most of them have foundations made of stone, brick masonry made of cement mortar which is then bound by reinforced concrete. According to SNI 7571:2010, this building quality has a maximum blasting vibration threshold value of 5 mm/s. The relationship curve between blasting vibrations or peak particle velocity (PPV) and the distance scale (SD) was successfully developed from the results of analysis of 30 blasting data. Based on this curve, it is predicted that the maximum total of explosives recommended to be safe at a distance of less than 300 m and at blasting vibration maximum 5 mm/s is 78.47 kg/delay.